2021
DOI: 10.2196/28731
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of the Stressor-Strain Process in Interns by Heart Rate Variability Measured With a Wearable and Smartphone App: Within-Subject Design Using Continuous Monitoring

Abstract: Background The emergence of smartphones and wearable sensor technologies enables easy and unobtrusive monitoring of physiological and psychological data related to an individual’s resilience. Heart rate variability (HRV) is a promising biomarker for resilience based on between-subject population studies, but observational studies that apply a within-subject design and use wearable sensors in order to observe HRV in a naturalistic real-life context are needed. Objec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
(100 reference statements)
2
15
0
Order By: Relevance
“…The seemingly more abiding impact of a change in resting HRV on the resting HRV of the subsequent days may also be influenced by the development of a negative feedback loop. A previous study showed that evening mental exhaustion negatively impacted subsequent resting HRV and that resting HRV itself buffered against the positive association between demands and stress, as well as between stress and mental exhaustion [ 38 ]. This aligns with the Conservation of Resources Theory, which describes that an initial loss of resources could lead to a negative feedback loop.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The seemingly more abiding impact of a change in resting HRV on the resting HRV of the subsequent days may also be influenced by the development of a negative feedback loop. A previous study showed that evening mental exhaustion negatively impacted subsequent resting HRV and that resting HRV itself buffered against the positive association between demands and stress, as well as between stress and mental exhaustion [ 38 ]. This aligns with the Conservation of Resources Theory, which describes that an initial loss of resources could lead to a negative feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a rough estimate of the extent to which the respective associations may be found across individuals can be described in order to guide future studies. The current methods were based on a prior study that investigated nested within-day associations [ 14 , 38 ]. Missing data are problematic for time-series analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HRV can be seen as a resource that enables cognitive and emotional regulation [ 17 ] and is physiologically depleted when dealing with demands [ 18 ]. Since HRV is associated with stress-buffering effects [ 19 , 20 ], its depletion may indicate a decline in resilience to cope with new demands and thus lead to unfavourable outcomes if a trend develops. This aligns with the conservation of resources theory, which suggests that an initial loss of resources can create a negative feedback loop that results in a loss spiral [ 21 ].…”
Section: Introductionmentioning
confidence: 99%